214 - PHYSICAL GROWTH PROFILE OF STUDENTS FROM PRIVATE SCHOOLS IN ARAGUAÍNA-TO. (Fiep Bulletin - online, 2011)
The evaluation of the body structure modifications related to physical growth, such as body structure and body mass, represent a major means of obtaining information of a population´s health condition. In this sense, the current research sought to answer the following question: What´s the physical growth profile of 7 – 10 year-old private school students in the city of Araguaína-TO? There were 329 children participating in this research, of which 173 were boys and 156 were girls. The growth was evaluated in both genders as the body mass and structure. The adequacy structure / age, weight / age was considered according to the reference values proposed by the National left for Health Statistics (NCHS-2002) and related them to the values of the one studied. For data analysis we used percentiles. The results revealed a normal profile in most of the students surveyed, showing a tendency for high weight and height. It emphasized the importance of measures of nutritional guidelines in schools designed to reduce and prevent cases of excess weight among school children to avoid future problems of health risk at older ages.
Keywords: Physical growth; body mass; height